MEASUREMENT OF FINANCIAL RISK TO ECONOMIC POLICY IN INDONESIA - Yoseva Maria Pujirahayu Sumaji (President University, 2021)
The world of economy is in a state of uncertainty as shown by the improvement in the projected growth of the world by international institutions. The state of development of the world economy is flutuative due to declining economic growth of developed and developing countries, lower commodity prices, and the difference in direction between monetary and fiscal policy. The development of the world economy can be seen from the Real Effective Exchange Rate (REER) indicator, which sees the exchange rate as a measure of the state of the world economy. This can attract investors to invest in Indonesia due to good REER conditions. REER can be used as one of the reference by investors to make investment decisions in the company that will later affect the company's decision-making. Decision-making will determine how far the company will experience the financial risks that will be set up in risk management. There are 120 non-financial companies registered with IDX Indonesia. The sampling techniques in this study used nonprobability sampling. The inferential statistical analysis conducted in this study is through classic assumption tests, regression analysis, mediation tests and hypothesis tests. The results of the study showed that the Risk Measurement of Economic Policy in Indonesia had a significant positive effect.